New-HOPLA--A Higher-Order Process Language with Name Generation - Winskel, Glynn; Nardelli, Francesco Zappa (BRICS Report Series, 2004)
This paper introduces new-HOPLA, a concise but powerful language for higher-order nondeterministic processes with name generation. Its origins as a metalanguage for domain theory are sketched but for the most part the paper concentrates on its operational semantics. The language is typed, the type of a process describing the shape of the computation paths it can perform. Its transition semantics, bisimulation, congruence properties and expressive power are explored. Encodings are given of well-known process algebras, including pi-calculus, Higher-Order pi-calculus and Mobile Ambients.